Pendampingan Penyusunan Biaya Produksi UMKM Kerupuk Susmi Desa Curah Cottok - Rachmawati, Dyna; Joewono, Andrew; Anggorowati, Adriana Anteng (FEB-UP Press, 2022)
Susmi Cracker SME is located in the village of Curah Cottok, Kapongan District, Situbondo Regency, East Java. The SME has been carrying out its operational activities since 2017. The main product of the SME is onion cracker. Operational activities of making onion crackers are still traditional. Onion crackers are sold in bulk form by being consignment with traders in the market and sold directly from homes which are also the places of business. The selling price per kilogram set by the Susmi Crackers SME is IDR 12,000. The determination of the selling price is based on the purchase of ingredients for making onion crackers. The cost calculation still ignores the cost of transportation in, production equipment, and direct labor. Currently, Susmi Cracker SME is taking the slicing equipment and oven rent offer from BUMDes Dharma Pitaloka. This mentoring activity helps Susmi Cracker SME in preparing their production costs appropriately. This assistance uses a visual method to make it easier for Mrs. Susmi as an SME owner to understand the concept of production costs. The production cost per kilogram is Rp 6.750. Selling price is Rp 12.000 per kg, so that the gross profit margin is Rp 5.250 per kg.